Monitoring of construction processes in the variable environment - Karlowski, Andrzej; Paslawski, Jerzy (Technological and Economic Development of Economy, 2008)
Interference problems of construction processes are especially disturbing due to their big scope of variability, uncertainty and complexity what significantly hinders planning and accomplishing the production processes on the building site. Monitoring of environment (which generates interference) and processes in progress enable to undertake activities aiming at introducing flexibility in managing of processes which may significantly increase the efficiency of systems ensuring quality in building. The described CONLI (CONcrete on‐LIne) system is an effective device of monitoring which enables the transfer of information in real time to different decision‐makers (e.g. site manager, supervision inspector, investor and the like) owing to wireless transmission and hybrid structure taking into account diverse scope of access depending on requirements of maintaining necessary data confidentiality. Statybos procesų stebėsena kintančioje aplinkoje Santrauka. Statybos procesų trikdžiai yra ypač pastebimi dėl savo didelio kintamumo, neapibrėžtumo ir kompleksiškumo. Jie daro dilelę įtaką planavimo ir vykdymo procesams. Aplinkos, sukeliančios trikdžių, ir vykstančių procesų stebėsena sudaro galimybę lanksčiau valdyti procesus, o tai labai pagerina statybos kokybę užtikrinančių sistemų veikimo efektyvumą. Aprašyta CONLI sistema, kuri yra efektyvi priemonė, leidžianti realiuoju laiku keistis informacija tarp įvairių sprendimų priėmėjų (pavyzdžiui, statybos vadovų, techninės priežiūros inspektorių, investuotojų ir pan.), turinčių bevielę duomenų perdavimo sistemą ir hibridinę struktūrą. Sistema užtikrina prieigą prie įvairios apimties informacijos ir garantuoja reikiamą jos konfidencialumą. Reikšminiai žodžiai: kontrolė, statybos valdymas, statybos procesas, lankstumas, betonavimas. First published online: 21 Oct 2010